Contributing to Communicable Diseases Intelligence Management in Canada: CACMID Meeting, March 2007, Halifax, Nova Scotia - Shamir Mukhi; Jeff Aramini; Amin Kabani (Canadian Journal of Infectious Diseases and Medical Microbiology)
In the spring of 2003, the Public Health Agency of Canada (then, Health Canada) partnered with several provincial/territorial and regional public health stakeholders to improve pan-Canadian public health surveillance, communications and response through the application of new technologies. This resulted in the creation of the Canadian Network for Public Health Intelligence (CNPHI), a comprehensive framework of applications and resources designed to fill critical gaps in Canada's national public health infostructure. Over the past four years, the CNPHI has evolved into Canada's only pan-Canadian public health information management system. With over 2000 registered users, the current CNPHI environment consists of more than 30 integrated applications and systems that can be loosely categorized into four functional groups: data exchange; data analysis and integration; communication, collaboration and coordination; and knowledge management. Despite poor data repositories, legacy information management systems, and the lack of standards and agreements, the CNPHI has demonstrated that much can be accomplished in these areas. Over the next decade, significant barriers impeding additional advances will be bridged through the implementation of the Electronic Health Record, and through ongoing efforts to address gaps in standards, and data- and information-sharing agreements. Together with new technologies coming on-line, opportunities to further enhance public health surveillance and response will be limited only by one's imagination.